2021
DOI: 10.3390/app11219988
|View full text |Cite
|
Sign up to set email alerts
|

Home Gardens as a Source of Medicinal, Herbal and Food Preparations: Modern and Historical Approaches in Lithuania

Abstract: The culture of home gardens in Lithuania comes from the deep traditions of agriculture. The purpose of this study was to collect and evaluate the ethnobotanical knowledge of medicinal plants grown in Tauragė District home gardens and to compare it with archival sources. A field survey was conducted from July 2019 to October 2020 in the Tauragė District, and the target group consisted of 27 respondents. The data obtained during the research were compared with the unpublished work of E. Šimkūnaitė, dated 1948. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The aboveground parts of the plants were most often selected by the study participants and the most popular method of preparation was tea ( Figure 5 ). While medicinal herbal teas are purposely consumed to treat a specific condition (i.e., cough) for a limited number of days, there is no limit to the duration for recreational teas as they are used within a food context, and not for the treatment of medical conditions [ 31 , 32 ]. Herbal beverages prepared as teas are consumed in a food context for their general social and/or recreational value or for their general attributions of being “healthy” drinks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aboveground parts of the plants were most often selected by the study participants and the most popular method of preparation was tea ( Figure 5 ). While medicinal herbal teas are purposely consumed to treat a specific condition (i.e., cough) for a limited number of days, there is no limit to the duration for recreational teas as they are used within a food context, and not for the treatment of medical conditions [ 31 , 32 ]. Herbal beverages prepared as teas are consumed in a food context for their general social and/or recreational value or for their general attributions of being “healthy” drinks.…”
Section: Resultsmentioning
confidence: 99%
“…In Eastern Europe, the most popular species was Rubus idaeus L. [ 33 ]; in our Pasvalys study, this trend was also confirmed. Herbs used as recreational teas, due to the Lithuanian climate, are also used to relieve colds and upper respiratory tract disorders and to strengthen their immunity [ 32 ]. Important sensory properties of recreational teas such as smell, flavor, and color must be suitable for making tea that has a tendency for long-term use.…”
Section: Resultsmentioning
confidence: 99%
“…Plants were also the primary therapeutic agents used by humans until the middle of the 19th century, and their value in medicine is still acknowledged today as sources of bioactive compounds for the development of drugs and health-promoting products [ 1 , 2 , 3 ]. Recent studies focusing on the US market show that herbal dietary supplements sales surpassed USD 10 billion for the first time in 2020 [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%